Peritoneal Dialysis in Neonates: A Five-Year Experience - Maliheh Kadivar; Razieh Sangsari; Kayvan Mirnia; Arash Abbasi; Motahareh Rabipour (Mashhad University of Medical Sciences, 2020)
Background: Peritoneal dialysis is an applicable method for children and even neonates. Moreover, it allows the quiet excretion of fluid and soluble substances without hemodynamic instability. Peritoneal dialysis can be continued easily in hospitalized infants. However, the question is whether peritoneal dialysis is an effective procedure to replace hemodialysis in neonates or not?Methods: The population of this study included all neonates who were admitted to the Neonatal Intensive Care Unit of Children's Medical Center Hospital, Tehran, Iran, and underwent peritoneal dialysis during 2012-17. The data were collected using a questionnaire. Subsequently, the underlying diseases, complications, and laboratory changes were determined before and after peritoneal dialysis.Results: In total, 29neonates who underwent peritoneal dialysis were evaluated in this study. Peritoneal dialysis was performed on 58.6% and 41.4 % of the cases for congenital metabolic disorder and extra body fluids, respectively. Moreover, electrolyte disorders and uremia were observed in 13.7% and 13.8% of the total cases, respectively. Several indications were seen in some infants. Dialysis failure was seen in 79.3% of the cases, most of which were due to dialysis catheter obstruction; however, the mean changes in potassium, sodium, urea, creatinine, acidosis, ammonia, and phosphorus were significant72 h after dialysis.Conclusion: This study showed that peritoneal dialysis faced several failures in newborns; however, metabolic disorders, electrolyte imbalance, uremia, and extra body fluid were resolved. Moreover, it is considered a vital and effective way for the treatment of newborns, especially in low-resource countries in which hemodialysis cannot be performed easily.